Direct Sourcing or Agent Sourcing? A Triadic Nash-Bargaining Optimization Framework for Liberian Firms Importing from China - Stephen, Enoch Ansumanah (Scientific Journal of Technology, 2025)
Many Liberian small and medium-sized enterprises (SMEs) source goods from China but face high transaction frictions, including supplier-search costs, quality and compliance risk, and limited bargaining leverage. This paper develops a triadic decision framework to evaluate whether Liberian importers should pursue Direct Sourcing (DS), where the buyer negotiates separately with the supplier and a service agent, or Agent Sourcing (AS), where a procurement agent coordinates upstream and downstream contracts. We integrate (i) a centralized benchmark under stochastic demand (Weibull), (ii) decentralized profit functions under DS and AS, and (iii) generalized Nash bargaining to obtain equilibrium wholesale and service prices as well as profit allocations. Using calibrated baseline parameters ( , agent cost , supplier cost compliance cost K=2; Weibull shape κ=2 and scale λ=100; bargaining powers α=0.4, β=0.3, γ=0.5), the centralized optimum yields total expected profit of 516 at q*=83.26. Under bargaining equilibrium, both DS and AS achieve the centralized total profit (channel coordination), but AS increases the buyer’s profit from 107.90 to 129.67 (about 20.2%) and produces a more balanced surplus split between agent and supplier. Sensitivity analysis shows that the AS advantage is robust across wide ranges of costs, demand scale, and bargaining power, with buyer–agent bargaining power being the strongest driver of the buyer’s relative gain. The results imply that AS is a rational and scalable strategy for Liberian SMEs when compliance complexity and information asymmetry are high; policy recommendations include strengthening accredited agent networks and reducing procedural trade costs.